On the Persuasiveness in Literary Texts - LAMBARJYAN, SRBUHI (Bulletin of Yerevan University H: Russian Philology, 2021)
The pa-per is devoted to some functions of the subjective category of persuasiveness.The proposed research deals with the role and abilities of persuasiveness in the construction of structure, semantic, philosophic and emotional content of literary and especially poetic texts.
Keywords: anthropocentrism, subjective (modal) categories, lingua-culturology, persuasiveness, texts of poetry and fiction